Adenomatous Neuroendocrine Tumors of the Middle Ear: A Multi-institutional Investigation of 32 Cases and Development of a Staging System. Issue 8 (September 2018) - Marinelli, John P.; Cass, Stephen P.; Mann, Scott E.; Haynes, David S.; Hunter, Jacob B.; Isaacson, Brandon; Sweeney, Alex D.; Pelosi, Stanley; Willcox, Thomas O.; O'Connell, Brendan P.; Rivera, Michael; Lane, John I.; et al.
Abstract : Objective: To date, less than 150 cases of middle ear adenomatous neuroendocrine tumors (MEANTs) have been reported in the English literature. The objective of this study was to provide a contemporary analysis of these rare lesions and develop a consensus-driven staging system. Study Design: Multi-institutional retrospective histopathologic, radiologic, and clinical review. Setting: Six tertiary referral centers. Patients: Thirty-two patients with pathologically confirmed MEANT. Intervention: Surgical resection, adjuvant therapy. Main Outcome Measures: Clinical manifestations, outcomes, staging system. Results: Patients commonly presented with progressive conductive or mixed hearing loss (90%), aural fullness (50%), and tonal tinnitus (46%). Pulsatile tinnitus (16%), carcinoid syndrome (4%), and facial nerve paresis (4%) were less commonly observed. MEANTs frequently mimicked temporal bone paraganglioma (31%) and cholesteatoma (15%) at presentation. According to a novel T/N/M/S staging system (S = secretory tumor) proposed herein, there were 6 (19%) T1, 19 (59%) T2, and 7 (22%) T3 MEANTs. T3 tumors were significantly more likely to undergo subtotal or near total resection compared with lower staged tumors secondary to adherence to critical neurovascular structures such as the petrous internal carotid artery and facial nerve ( p  = 0.027). Patients with T3 MEANTs were more likely to experience multiple recurrences, require adjuvant therapy with a somatostatin analogue, or develop permanent facial nerve paresis compared with lower staged tumors. At last follow up, no patients with T1 MEANTs had developed recurrence, whereas 37% (7/19) of patients with T2 MEANT and 57% (4/7) of patients with T3 MEANT experienced either disease recurrence after gross total resection (GTR) or regrowth of known residual tumor requiring additional surgery at a median duration of 72 months (95% CI, 24–84). Conclusions: Patients with MEANTs can present with nonspecific symptomatology that overlaps with more commonly encountered middle ear lesions. MEANT exhibits a proclivity for recurrence according to T-stage and long-term clinical follow up is necessary, particularly for advanced stage tumors.